Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian HP iPhone - Sri Mulyati; Umban Adi Jaya (Institut Manajemen Wiyata Indonesia, 2020)
This study aims to examine the effect of product quality and price on purchasing decisions for iPhone brand HP products in Sukabumi City. This type of research is categorized as a descriptive study using a quantitative approach. The population of this research is iPhone users in Sukabumi City. The research sample consisted of 100 respondents. Data collection using a questionnaire. Testing the quality of the instrument using the validity test and reliability test. The next test is testing the fulfillment of classical assumptions and multiple linear regression analysis, including t statistical testing and F statistics. The results of the study found that partially and simultaneously product quality and price variables have a positive and significant effect on purchasing decision variables. Respondents view the performance of the HP iPhone brand is very good, the price is in accordance with the quality and benefits provided.